Electronic Structure and Triplet–Triplet Energy Transfer in Artificial Photosynthetic Antennas1. (11th August 2018) - Tejeda‐Ferrari, Marely E.; Brown, Chelsea L.; Coutinho, Gabriela C. C. C.; Gomes de Sá, Ghabriel A.; Palma, Julio L.; Llansola‐Portoles, Manuel J.; Kodis, Gerdenis; Mujica, Vladimiro; Ho, Junming; Gust, Devens; Moore, Thomas A.; Moore, Ana L.
Abstract: Three Pd(II) phthalocyanine–carotenoid dyads featuring chromophores linked by amide bonds were prepared in order to investigate the rate of triplet–triplet (T‐T) energy transfer from the tetrapyrrole to the covalently attached carotenoid as a function of the number of conjugated double bonds in the carotenoid. Carotenoids having 9, 10 and 11 conjugated double bonds were studied. Transient absorption measurements show that intersystem crossing in the Pd(II) phthalocyanine takes place in 10 ps in each case and that T‐T energy transfer occurs in 126, 81 and 132 ps in the dyads bearing 9, 10 and 11 double bond carotenoids, respectively. To identify the origin of this variation in T‐T energy transfer rates, density functional theory (DFT) was used to calculate the T‐T electronic coupling in the three dyads. According to the calculations, the primary reason for the observed T‐T energy transfer trend is larger T‐T electronic coupling between the tetrapyrrole and the 10‐double bond carotenoid. A methyl group adjacent to the amide linker that connects the Pd(II) phthalocyanine and the carotenoid in the 9 and 11‐double bond carotenoids is absent in the 10‐double bond carotenoid, and this difference alters its electronic structure to increase the coupling. Abstract : Three Pd(II) phthalocyanine–carotenoid dyads with the two chromophores linked by amide bonds were prepared to study the triplet–triplet (T‐T) energy transfer from the tetrapyrrole to the carotenoid as a function of the number of conjugated double bonds in the carotenoid. Experimentally T‐T energy transfer was found to be faster in the 10 double bond carotenoid than in ones having 9 or 11 double bonds. DFT calculations indicated that the methyl group on the polyene chain adjacent to the amide linker was a primary structural feature that modulates the T‐T electronic coupling and therefore the T‐T energy transfer rate.